RADIOLOGIC PRESENTATION OF COVID-19 PNEUMONIA - Đurić-Stefanović, Aleksandra (Srpski medicinski časopis Lekarske komore, 2021)
Interstitial pneumonia is main manifestation of COVID-19 disease. The aim of this paper is to present the spectrum of typical radiological (CT and radiographic) findings of COVID-19 pneumonia, CT examination techniques, types and evolution of inflammatory lesions in the lungs, criteria for assessing the probability of COVID-19 pneumonia in comparison to other interstitial pneumonias, scoring systems to determine the extent of COVID-19 pneumonia based on CT findings and radiography. The standard CT examination protocol is a native CT examination of the chest, and due to high sensitivity of low-dose CT protocols for detecting lung lesions, this imaging technique became widely used in radiological practice during the COVID-19 pandemic. Bilateral, multiple round or confluent zones of “ground glass” density, predominantly localized subpleurally, peripherally and posteriorly, usually most extensive in the lower lobes, represent a typical CT presentation of COVID-19 pneumonia. Consolidations may develop at a later stage. A chest X-ray shows homogeneously reduced transparency in the lateral pulmonary fields, circular and irregular cloudy shadows, and confluent patchy shadows, usually the most extensive basally and laterally. RSNA and CO-RADS criteria are used to assess the probability of COVID-19 pneumonia based on the criteria of a typical/atypical CT finding. According to time dynamics of inflamatory lung lesions presentation, four stages of COVID-19 pneumonia were defined: early, progressive, consolidation and organization. To assess the extent and severity of pneumonia, various scoring systems have been proposed, the most widely accepted being the CT severity scoring system based on visual, semiquantitative assessment of the percentage of lung parenchyma involvement of each of the five lung lobes by inflammatory lesions on a scale of 1 (75%), so the maximum score can be 25.
Keywords: COVID-19 pneumonia; computed tomography; chest X-ray